Highly Selective and Stable Cu Catalysts Based on Ni–Al Catalytic Systems for Bioethanol Upgrading to n-Butanol - Yan Xiao; Nannan Zhan; Jie Li; Yuan Tan; Yunjie Ding (Molecules, 2023)
The catalytic upgrading of ethanol into butanol through the Guerbet coupling reaction has received increasing attention recently due to the sufficient supply of bioethanol and the versatile applications of butanol. In this work, four different supported Cu catalysts, i.e., Cu/Al2O3, Cu/NiO, Cu/Ni3AlOx, and Cu/Ni1AlOx (Ni2+/Al3+ molar ratios of 3 and 1), were applied to investigate the catalytic performances for ethanol conversion. From the results, Ni-containing catalysts exhibit better reactivity; Al-containing catalysts exhibit better stability; but in terms of ethanol conversion, butanol selectivity, and catalyst stability, a corporative effect between Ni–Al catalytic systems can be clearly observed. Combined characterizations such as XRD, TEM, XPS, H2-TPR, and CO2/NH3-TPD were applied to analyze the properties of different catalysts. Based on the results, Cu species provide the active sites for ethanol dehydrogenation/hydrogenation, and the support derived from Ni–Al–LDH supplies appropriate acid–base sites for the aldol condensation, contributing to the high butanol selectivity. In addition, catalysts with strong reducibility (i.e., Cu/NiO) may be easily deconstructed during catalysis, leading to fast deactivation of the catalysts in the Guerbet coupling process.